A successful long-term relationship: Three years of LTI integrations in Canvas. Issue 4 (1st December 2020) - Wharton, Lindsey; Pritchard, Michael
Abstract: As Florida State University transitioned to Canvas in 2017, the Distance Library Services team planned and implemented Springshare LTI, subject-specific Library Tools within the Learning Management System. These tools present invaluable teaching and learning opportunities for the libraries within digital classrooms and offer options for connecting students to library staff and services. With heightened interest from the distance library community in LMS integration, the goal of this paper is to examine an experience with LTI integration after three years of partnership. Furthermore, recommendations will be offered for other libraries interested in implementing LTI integrations in their LMS to support distance learning and on-campus populations.